Caracterização de detonação de um motor de combustão interna com ondas mecânicas - Joao Batista Carvalho Filardi (2013)
The so-called knock phenomenon in spark ignition reciprocating engines still presents major design challenges even after almost a century of intensive research. Knocking is an indication of severe operational conditions which are detrimental to performance and may also result in extensive damage to the engine. Knock, is basically the term used to describe the noise that is transmitted through the structure of the engine when spontaneous ignition of the unburned portion of the gas takes place. This work describes the methodology developed for the characterization of this phenomenon in a single cylinder research engine. This, besides the analytical approach by graphic solution from the wave equation, uses parameters vibroacustics for detecting pressure waves generated within the combustion chamber and which propagate through the structure of the engine as vibrational waves. The finite element method (FEM) is also used as support for a better understanding of this phenomenon. The results also indicate the most suitable type of sensor to detect knock also indicate this methodology allows engineers and technicians to find better performances of this engine, considering the different configurations of fuel injection systems, the diverse types of flow structures and the main types of alternative fuels used in the researches.